0==>x\in(0;+\infty);\\
t=\log_2x;\\
x=2^t;\\
t^2-2t-3=0;\\
D=(-2)^2+4\cdot1\cdot(-3)=4+12=16=(\pm4)^2;\\
t_1=\frac{2-4}{2}=-\frac22=-1;\ x=2^{-1}=\frac12;\\
t_2=\frac{2+4}{2}=\frac{6}{2}=3;\ x=2^3=8;\\
t^2-2t-3\geq0==>t\in(-\infty;-1]\cup[3;+\infty);\\
\left(\log_2x\right)^2-2\log_2x-3\geq0==>x\in(0;\frac12]\cup[8;+\infty)." alt="\left(\log_2x\right)^2-2\log_2x-3\geq0;\\
D(f):\ x>0==>x\in(0;+\infty);\\
t=\log_2x;\\
x=2^t;\\
t^2-2t-3=0;\\
D=(-2)^2+4\cdot1\cdot(-3)=4+12=16=(\pm4)^2;\\
t_1=\frac{2-4}{2}=-\frac22=-1;\ x=2^{-1}=\frac12;\\
t_2=\frac{2+4}{2}=\frac{6}{2}=3;\ x=2^3=8;\\
t^2-2t-3\geq0==>t\in(-\infty;-1]\cup[3;+\infty);\\
\left(\log_2x\right)^2-2\log_2x-3\geq0==>x\in(0;\frac12]\cup[8;+\infty)." align="absmiddle" class="latex-formula">
Ответ: